2020
DOI: 10.1021/acsnano.0c00708
|View full text |Cite
|
Sign up to set email alerts
|

Icaritin Exacerbates Mitophagy and Synergizes with Doxorubicin to Induce Immunogenic Cell Death in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) resistant to both chemotherapy and immunotherapy is among the deadliest malignancies. Doxorubicin widely used in transarterial chemotherapy in HCC can induce immunogenic cell death (ICD), but the resulting immunogenicity is still weak. We aim to seek a strategy for improving the efficacy of ICD in HCC based on an immunoregulatory drug called icaritin. Icaritin induced mitophagy and apoptosis to provoke ICD both in mouse Hepa1−6 and human Huh7 HCC cells. A combination of icaritin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
184
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(184 citation statements)
references
References 40 publications
0
184
0
Order By: Relevance
“…On the one hand, inhibition of the mitophagic axis enhances tumor necrosis factor-based immunotherapy to control the survival and progression of cervical and gastric cancer cells (Yan et al, 2018;Zhao et al, 2019). On the other hand, enhanced mitophagy may induce immunogenic cell death, thereby inhibiting tumor growth through the activation of cytotoxic T lymphocytes in liver cancer cells (Yu et al, 2020). These findings further support that mitophagy may be an effective target for modified tumor immunotherapy.…”
Section: Mitophagy and Tumor Therapiesmentioning
confidence: 60%
“…On the one hand, inhibition of the mitophagic axis enhances tumor necrosis factor-based immunotherapy to control the survival and progression of cervical and gastric cancer cells (Yan et al, 2018;Zhao et al, 2019). On the other hand, enhanced mitophagy may induce immunogenic cell death, thereby inhibiting tumor growth through the activation of cytotoxic T lymphocytes in liver cancer cells (Yu et al, 2020). These findings further support that mitophagy may be an effective target for modified tumor immunotherapy.…”
Section: Mitophagy and Tumor Therapiesmentioning
confidence: 60%
“…The late apoptotic release of nucleus‐localizing high mobility group box 1 (HMGB1) binds TLR2 and TLR4 on DCs, stimulates pro‐inflammatory cytokines production, and induces DCs maturation. [ 54 ] For the untreated cells or cells incubated with nanosheets alone, HMGB1 was mostly located in cell nuclei. A significant translocation of HMGB1 from nuclei to the extracellular milieu was observed in the cells following nanosheets plus NIR treatment (Figure 2f).…”
Section: Resultsmentioning
confidence: 99%
“…demonstrated that through the induction of mitophagy and apoptosis, icaritin can motivate and promote ICD within both mouse and human HCC cells ( Figure ). [ 121 ] Just given a low dose of icaritin and doxorubicin, the synergistic NPs rebuilt immunosuppressive microenvironment and caused strong immune memory in the body. Icaritin induces both apoptosis and mitophagy and subsequently activates ICD relative biomarkers in HCC tumor cells.…”
Section: Therapeutic Advances For Hcc Managementmentioning
confidence: 99%